Persepsi Penggunaan QRIS (Quick Response Code Indonesian Standard) sebagai Sistem Pembayaran di Edie Arta Motor Cabang Imam Bonjol - Melkianus, Febriana Wenny; Dharmayasa, Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to determine the perception of using QRIS (Quick Response Code Indonesian Standard) as a payment system at Edie Arta Motor Imam Bonjol Branch. The population in this study is consumers who use QRIS at Edie Arta Motor Imam Bonjol Branch. The number of samples used is the number of indicators multiplied by 5-10. The sampling technique in this study is sampling probability. The data in this study was collected by distributing questionnaires. The analysis techniques used are descriptive statistics and inferential statistics. The results of the study show that the public's perception of the use of QRIS as a payment system at Edie Arta Motor Imam Bonjol Singaraja Branch has a positive effect. Risk perception shows a positive influence on the use of QRIS as a payment system. The perception of ease of use also shows a positive influence, and the perception of benefits has a positive influence on the use of QRIS as a payment system at Edie Arta Motor Imam Bonjol Singaraja Branch. The conclusion of this study is that QRIS is well received by consumers and is considered useful and easy to use, although there are some perceived risks.